2011
DOI: 10.3892/or.2011.1141
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of podoplanin in benign and malignant soft tissue tumors: Immunohistochemical and quantitative real-time RT-PCR analysis

Abstract: Abstract. Podoplanin is a 38 kDa mucin-type transmembrane glycoprotein that was first identified in rat glomerular epithelial cells (podocytes). It is expressed in normal lymphatic endothelium, but is absent from vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…In humans, podoplanin staining in the absence of cytokeratin staining can be seen in several different sarcomas as well as in malignant mesothelioma [34,97]. The malignant serosal tumors seen in this study were morphologically consistent with malignant sarcomatous mesotheliomas with five of the six tumors involving multiple peritoneal serosal surfaces.…”
Section: Discussionsupporting
confidence: 51%
“…In humans, podoplanin staining in the absence of cytokeratin staining can be seen in several different sarcomas as well as in malignant mesothelioma [34,97]. The malignant serosal tumors seen in this study were morphologically consistent with malignant sarcomatous mesotheliomas with five of the six tumors involving multiple peritoneal serosal surfaces.…”
Section: Discussionsupporting
confidence: 51%
“…The present study also showed both the cytoplasmic and membrane positivity being higher in all the grades of SCC when compared to the only membrane positivity and this high expression could be attributed to the expression of podoplanin at the protein and mRNA levels. [ 18 ] Overall podoplanin expression was high in MDSCC when compared to PDSCC and WDSCC thereby reflecting the immature status in the differentiation process of SCC.…”
Section: Discussionmentioning
confidence: 99%
“…PDPN is also expressed by normal kidney podocytes [15], alveolar type I cells [16], basal epidermal keratinocytes [17], and mesothelial cells [18,19]. Several types of cancer may also express PDPN, such as squamous cell carcinomas [20,21], soft tissue tumors [22], and brain tumors [23]. PDPN-expressing cancer cells have enhanced malignant potential due to enhancement of platelet aggregation, which promotes metastasis [24,25], alteration of cell morphology and motility [26,27], and epithelial-mesenchymal transition [28].…”
Section: Introductionmentioning
confidence: 99%